Operations of the Institution of Baitul Mal Wa At-Tamwil under the Perspective of al-Kulliyat al-Khamsah of the al-Shatibi’s Maqasid al-Shari‘ah - Iftihor Iftihor (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2021)
The development of the Islamic economics in Indonesia shows progress and needs to be appreciated. It can be seen in the effort to find its relevance to the modern economy, including the application of maqasid shari'ah as the main support in every operational development of shari’ah financial institutions. In this study, researcher will focus on the issue of how to implement the maintenance of al-kulliyyat al-khamsah of maqasid shari'ah of al-Shatibi at BMT Mawaddah Pelenggagan, Pamekasan, Madura. This is a qualitative research that the data is gained by using documentation and interview technique. The results of this study are (1) the implementation of maintenance of maqasid shari'ah of al-Shatibi’s al-kulliyyat al-khamsah which has been carried out by BMT Mawaddah has been going well. (2) There are several patterns that are not implemented because there are obstacles in their implementation. (3) It is found that there is a form of conformity between the concept of maqasid shari'ah in general and that of al-Shatibi’s al-kulliyyat al-khamsah.